Fluids intake between normalweight children and metabolically healthy obese children: a comparative review - Benítez-Porres, Javier; Morente-Oria, Honorato Fernando; Romance-García, Ángel Ramón; Bernal-López, María Rosa (My University, 2018)
The relationship between obesity and fluid intake in children has been poorly studied. There are few results in the literature that help us to identify those mechanisms that influence the hydration level in school population.
Comparativa en la ingesta de fluidos entre niños con normopeso y niños obesos metabólicamente sanos
Keywords: Hidratación; Hydration; Obesity; Nutrition; Childhood